Role of Vitamin E in Ischaemic Skin Flap Survival in Rats - Khazanchi, Rakesh K; Pal, Sujoy; Mital, Deepak; Gupta, Kalpana; Guleria, Sandeep; Nanda, Vipul (Indian Journal of Plastic Surgery, 1995)
The efficacy of free radical scavenger – Vitamin E (VE) in salvage of ischaemic skin flaps was studied in an experimental rat skin flap model. The animals were divided into two groups – a control group (N=15) who did of receive VE and a test group (N=15) who received VE starting one week preoperatively. No significant difference was found in flap necrosis between the control group (38.365% ± 1.398% SEM) and the test group (35.288% ± 0.635% SEM), which received therapeutic dose of VE (100 mg/kg/day. 1 mg = 1.49 I.U). Further research is needed to establish the role of vitamin E as an agent of ischaemic skin flap salvage.